2015
DOI: 10.1016/j.indcrop.2014.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis of in vitro cultures of Miscanthus × giganteus cultivar Freedom and detecting polymorphisms of regenerated plants using ISSR markers

Abstract: Giant miscanthus (Miscanthus x giganteus; Mxg) is a key candidate energy crop for use in biomass to liquid fuel production. It is a naturally seed sterile triploid lacking genetic variation, the basis for selection. Therefore, induced mutation techniques are particularly important in Mxg. The objective of this research was to induce variation in Freedom, an elite cultivar, through in vitro chemical mutagenesis. A previously-optimized in vitro propagation protocol for Freedom was used following the in vitro mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 40 publications
(51 reference statements)
1
20
0
Order By: Relevance
“…The results of genetic divergence corroborate with the results obtained by Cheruvathur et al (2012), where the analysis of ISSR data in nine plants regenerated in vitro from R. nasutus callogenesis and the mother plant, the use of 12 ISSR markers indicated low genetic variability. In a study with ISSR markers in plants regenerated in vitro from the callogenesis, Perera et al (2015) concluded that these are useful in detecting polymorphisms in Miscanthus × Giganteus and can be used for generation and screening of mutants leading to the development of new cultivars.…”
Section: Molecular Analysismentioning
confidence: 99%
“…The results of genetic divergence corroborate with the results obtained by Cheruvathur et al (2012), where the analysis of ISSR data in nine plants regenerated in vitro from R. nasutus callogenesis and the mother plant, the use of 12 ISSR markers indicated low genetic variability. In a study with ISSR markers in plants regenerated in vitro from the callogenesis, Perera et al (2015) concluded that these are useful in detecting polymorphisms in Miscanthus × Giganteus and can be used for generation and screening of mutants leading to the development of new cultivars.…”
Section: Molecular Analysismentioning
confidence: 99%
“…For abiotic stress treatments, it is more convenient to control the culture conditions than in the field environment [20,40]. Salt, drought, cold, and heavy metal tolerance have been successfully performed in many plants.…”
Section: Availability To Use Some Selective Agents In Culture Conditionsmentioning
confidence: 99%
“…Morphological and physiological changes should be used in combination to discriminate the mutants. All the parameters such as leaf injury, slower growth, average number of shoots per explant, survival percentage of the plants, fresh weight of the explants, leaf photosynthetic capacity, antioxidant defense system, and accumulation of osmolytes should be investigated in detail especially for stress tolerance studies [40,41].…”
Section: New Insights On Gamma Raysmentioning
confidence: 99%
See 1 more Smart Citation
“…Freedom and Illinois, originated from a single genotype via vegetative propagation. Therefore, indirect regeneration procedures might enable generation of additional desired mutations (Perera et al 2015) and ploidy manipulations (Yu et al 2009), leading to new cultivar development.…”
Section: Introductionmentioning
confidence: 99%